Impact of Diversity Management Practices on Performance of Teachers in Higher Education Sector - Rani, Neha; Goel, Anuj (Journal of Commerce and Trade, 2021)
Now a days, workplace has become place of diverse and multi cultural in each organization even in higher educational institutions. This study analyzes how employee pay is related to educational diversity, that is, variability in the formation of work groups in terms of different types of vocational education and training. As previous research shows that a variety of variants have positive effects on work, the positive effect due to 'educational diversity' also seems plausible. The following categories of diversity namely nationality, race, language, disability and gender were admired the most effective and efficient in higher education higher education. Research results have shown that there is a clear correlation between institutional members and diversity and why it should be regulated. This study also showed that institutions are making good progress in controlling diversity. The discovery of this work on the governance of diverseness (diversity management) are in these institutions that there is a non-fulfillment by higher independent educational institutions to communicate effectively and efficiently through diversified policies and strategies for all members of the organization and the failure to ensure equality regarding gender representation in management levels. Several recommendations were proposed to improve diversity and diversity management processes. A constructed questionnaire has been used for facts gathering and collection.